2020
DOI: 10.1371/journal.pone.0236891
|View full text |Cite
|
Sign up to set email alerts
|

The loss of STAT3 in mature osteoclasts has detrimental effects on bone structure

Abstract: Signal Transducer and Activator of Transcription 3 (STAT3) has recently been shown to be involved in bone development and has been implicated in bone diseases, such as Job's Syndrome. Bone growth and changes have been known for many years to differ between sexes with male bones tending to have higher bone mass than female bones and older females tending to lose bone mass at faster rates than older males. Previous studies using conditional knock mice with Stat3 specifically deleted from the osteoblasts showed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
(69 reference statements)
0
10
0
Order By: Relevance
“…Recently, several studies have shown that different factors are involved during the osteoclastogenesis process [ 46 ]. This process leads to maturation and differentiation of osteoclasts from the monocyte/macrophage lineage.…”
Section: Jak/stat and Bone Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies have shown that different factors are involved during the osteoclastogenesis process [ 46 ]. This process leads to maturation and differentiation of osteoclasts from the monocyte/macrophage lineage.…”
Section: Jak/stat and Bone Cellsmentioning
confidence: 99%
“…Moreover, in a very recent study conducted by Davidson et al, it is highlighted that the participation of STAT3, during the regulation of the osteoclastogenic process, occurs in a different way in female than male osteoclastic cells. So, these data suggest that the STAT3 signal may have a key role in bone turnover [ 46 , 84 , 85 ]. Initially, an inactivating STAT3 mutation was found, which leads to a disease called Job syndrome.…”
Section: Implication Of Jak/stat In Bone Metabolismmentioning
confidence: 99%
“…While transcriptome analysis of developing OC has been previously reported at >24h post-RANKL exposure ( An et al., 2014 ; Bae et al., 2017 ; Davidson et al., 2020 ; Park-Min et al., 2014 ), the immediate transcriptional responses triggered by RANKL have not been explored yet. Therefore, to capture the first transcriptional waves during RANKL-driven OC lineage commitment, we performed RNA-seq of RAW264.7 cells at 0, 4, 14, and 24h upon RANKL, I-BET151, and RANKL + I-BET151 treatment ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…This is normally the consequence of increased bone resorption and decreased bone formation. Besides, more evidence suggested that bone-selective STAT3 knockout mice indicated an osteoporotic phenotype [ 48 , 49 ]. With regard to its role in vessel formation, the association between STAT3 and neovascularization has been widely elucidated.…”
Section: Discussionmentioning
confidence: 99%